Beyond the Conventional Wisdom: A Reply to Sher & Sher (1994) - Ivan Searston (Journal of Research in Rural Education, 1995)
Jonathan and Katrina Sher have constructed a scaffold that could underpin rural development in broad terms, redress the marginalisation ofrural people, and treat them as if they really mattered. Moves in the directions espoused by the Shers are detectable in recent Australian government policy. However, in the Australian literature, the term regional rather than rural is occurring more frequently. Confusion between what is regional and what is rural Australia could lead to initiatives that assist rural communities that are being usurped by regional centres masquerading as rural. Policymakers are failing to appreciate that this confusion will further marginalise the real rural communities.